Studies in classic American literature - Lawrence, David Herbert, 1885-1930. (New York ; Cambridge)
lxxix, 632 s.
Keywords: "Studies in Classic American Literature, first published in 1923, provides a cross-section of D. H. Lawrence's writing on American literature, including landmark essays on Benjamin Franklin, James Fenimore Cooper, Edgar Allan Poe, Nathaniel Hawthorne, Herman Melville and Walt Whitman. Eight of the essays were first published in the English Review 1918–19; but Lawrence continued to work on his material, with the aim of producing a full-length book; at various times fifteen separate items belonged to it, all of them revised on different occasions, some of them four or five times, and often corrected with the errors of their predecessors preserved. This volume offers the final 1923 version of the text in a newly corrected and uncensored form, and the complete surviving text of the essays of the English Review period, as well as a host of other materials, including four different versions of Lawrence's pioneering essay on Whitman." --